A review of climate change implications for built environment: Impacts, mitigation measures and associated challenges in developed and developing countries. (20th February 2019) - Andrić, Ivan; Koc, Muammer; Al-Ghamdi, Sami G.
Abstract: This interdisciplinary review organizes, summarizes and critically analyzes the literature regarding the nexus between climate change and the built environment, its associated impacts, and the proposed mitigation measures and challenges for their implementation. While global warming-driven changes of ecosystems could have multiple impacts on the built environment (most prominently on building energy demand and related urban energy systems), the building sector presents significant potential for climate change mitigation. Study findings indicate that building renovations have significant potential for the mitigation of urban-related emissions and achieving the sustainability goals set. However, these measures should be adapted to different climate conditions and different segments of the building stock. In developed countries, where the majority of the building stock is older than 50 years, more effort should be invested into creating adequate policies for the renovation of existing building stock. In developing countries with rapid growth in the urban environment, due to a previous lack of energy-efficiency policies, the focus should be on policy development and an increase in environmental awareness among building owners/tenants. Moreover, additional research efforts should be invested into performing technoeconomic and environmental analyses of green wall performance under future climate conditions, especially within the hot and humid climates.